Plasticity in striatopallidal projection neurons mediates the acquisition of habitual actions. (30th June 2015) - Shan, Qiang; Christie, MacDonald J.; Balleine, Bernard W.
Abstract In instrumental conditioning, newly acquired actions are generally goal‐directed and are mediated by the relationship between the action and its consequences or outcome. With continued training, however, the performance of such actions can become automatic, reflexive or habitual and under the control of antecedent stimuli rather than their consequences. Recent evidence suggests that habit learning is mediated by plasticity in the dorsolateral striatum (DLS). To date, however, no direct evidence of learning‐related plasticity associated with overtraining has been reported in this region, nor is it known whether, or which, specific cell types are involved in this learning process. The striatum is primarily composed of two classes of spiny projection neurons, the striatonigral and striatopallidal spiny projection neurons, which express dopamine D1 and D2 receptors, and control direct and indirect pathways, respectively. Here we found evidence of a post‐synaptic depression in DLS striatopallidal projecting neurons in the indirect pathway during habit learning in mice. Moreover, this training‐induced depression occluded post‐synaptic depression induced by co‐activation of D2 receptors and transient receptor potential vanilloid 1 (TRPV1) channels, implying that this pathway is involved in habit learning. This hypothesis was further tested by disrupting this signal pathway by knocking out TRPV1 channels, resulting in compromised habit learning. Our findings suggest that post‐synaptic plasticity at D2 neurons in the DLS mediates habit learning and, by implicating an interaction between the D2 receptor and TRPV1 channel activity, provide a potential drug target for influencing habitual action control.